Answer:
Cost of one bush is $23
Cost of one tree is $47
Step-by-step explanation:
Let cost of one bush be x
Cost of one tree be y
Total cost of first order was $487
Total cost of second order was $232
We know that
13x + 4y = 487...............................................(1)
6x +2y = 232 or 3x + y = 116
y = 116 - 3x......................................................(2)
Substituting y's value obtained in equation (2) in equation (1) we get,
13x + 4(116-3x) = 487
487 = 13x + 464 - 12x
x = 23
Cost of one bush is $23
Substitute x's value in equation (2) to get value of y
y = 116 - 3(23)
= 47
Cost of one tree is $47